Jorid Linvik's big book of knitted socks : 45 distinctive Scandinavian patterns - Linvik, Jorid (Trafalgar Square Books, 2017)
"Scandinavian knitwear designer Jorid Linvik's 45 creative, charming sock designs come in a rainbow of colors and interesting patterns, from simple stripes to flowers, animals and characters. Understand the basics of planning, sizing, and making your own fabulous socks, and then dive into an incredible selection of pre-charted patterns - dozens of delightful designs in multiple sizes, for children and adults. There's something here that's the perfect fit for any foot: bright and bold or classic and comfortable, covered in cozy cats or a pair of dancing elephants! Includes beautiful full-color photographs, plus hints, tips, and tricks that make sock-knitting a cinch."--Amazon.